Improvement of Imiquimod Solubilization and Skin Retention via TPGS Micelles: Exploiting the Co-Solubilizing Effect of Oleic Acid - Martina Ghezzi; Silvia Pescina; Andrea Delledonne; Ilaria Ferraboschi; Cristina Sissa; Francesca Terenziani; Paula De Freitas Rosa Remiro; Patrizia Santi; Sara Nicoli (MDPI AG, 2021)
Imiquimod (IMQ) is an immunostimulant drug approved for the topical treatment of actinic keratosis, external genital-perianal warts as well as superficial basal cell carcinoma that is used off-label for the treatment of different forms of skin cancers, including some malignant melanocytic proliferations such as lentigo maligna, atypical nevi and other in situ melanoma-related diseases. Imiquimod skin delivery has proven to be a real challenge due to its very low water-solubility and reduced skin penetration capacity. The aim of the work was to improve the drug solubility and skin retention using micelles of d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS), a water-soluble derivative of vitamin E, co-encapsulating various lipophilic compounds with the potential ability to improve imiquimod affinity for the micellar core, and thus its loading into the nanocarrier. The formulations were characterized in terms of particle size, zeta potential and stability over time and micelles performance on the skin was evaluated through the quantification of imiquimod retention in the skin layers and the visualization of a micelle-loaded fluorescent dye by two-photon microscopy. The results showed that imiquimod solubility strictly depends on the nature and concentration of the co-encapsulated compounds. The micellar formulation based on TPGS and oleic acid was identified as the most interesting in terms of both drug solubility (which was increased from few µg/mL to 1154.01 ± 112.78 µg/mL) and micellar stability (which was evaluated up to 6 months from micelles preparation). The delivery efficiency after the application of this formulation alone or incorporated in hydrogels showed to be 42- and 25-folds higher than the one of the commercial creams.